2020
DOI: 10.1155/2020/8820259
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Motivation in Teaching: Relations with Social Support Climate, Teacher Efficacy, Emotional Exhaustion, and Job Satisfaction

Abstract: This study explored how teachers' peer support climate (PSC) and supervisory support climate (SSC) were related to teacher self-efficacy (TSE), teacher job satisfaction (TJS), teacher emotional exhaustion (TEE), and motivation to quit the teaching profession (MQTP) among teachers in the Philippines. Participants were 457 teachers in the Central Visayas Region. Structural equation modeling (SEM) indicated that MQTP varies as to self-efficacy, emotional exhaustion, and job satisfaction. Responses among all const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 47 publications
(99 reference statements)
1
8
0
Order By: Relevance
“…(2020) suggest that teachers' motivation plays a vital role in technological integration in mathematics classrooms. Thus, there is a need to craft policy directions to enhance teaching technical aspects, especially that support climates are an essential dimension of motivation to teach among Filipino teachers (Gonzales, Gonzales, Costan & Himang, 2020). Another result supporting our findings is the work of Van Laer, Beauchamp and Colpaert (2012), which revealed that teachers' TK is a relevant predictor for IWBs in schools.…”
Section: Discussionsupporting
confidence: 81%
“…(2020) suggest that teachers' motivation plays a vital role in technological integration in mathematics classrooms. Thus, there is a need to craft policy directions to enhance teaching technical aspects, especially that support climates are an essential dimension of motivation to teach among Filipino teachers (Gonzales, Gonzales, Costan & Himang, 2020). Another result supporting our findings is the work of Van Laer, Beauchamp and Colpaert (2012), which revealed that teachers' TK is a relevant predictor for IWBs in schools.…”
Section: Discussionsupporting
confidence: 81%
“…The results showed that teachers with more exposure to professional development and more efficacious teachers tended to have higher levels of job satisfaction. Recent studies also found a positive relationship between teaching self-efficacy and job satisfaction among teachers in China (Wang et al, 2015;Li et al, 2017), Iran (Alibakhshi et al, 2020), Norway (Zakariya, 2020), and Philippine (Gonzales et al, 2020). However, studies on teaching self-efficacy and job satisfaction at the university level are minimal.…”
Section: Ctse and Job Satisfactionmentioning
confidence: 98%
“…Teachers with greater self-efficacy put more energy into their job, have higher levels of job satisfaction, and develop interpersonal networks to sustain their job satisfaction (Caprara et al, 2006;Klassen et al, 2013;Perera et al, 2019;Alibakhshi et al, 2020;Gonzales et al, 2020;Toropova et al, 2021). Extensive research found a positive correlation between teaching selfefficacy and job satisfaction among K-12 teachers (Klassen and Chiu, 2010;Soto and Rojas, 2019;Zakariya, 2020).…”
Section: Ctse and Job Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The teaching profession is frequently characterised as one of the most stressful professional domains because of some several factors including school conditions, social support climates, policy directions and learners' particularities (Day et al, 2007;Gavish & Friedman, 2010;Harmsen et al 2018;Johnson et al, 2005;Neves de Jesus & Lens, 2005;Stoeber & Rennert, 2008;Skaalvik & Skaalvik, 2015). Perceived heavy workload is related to low professional motivation, emotional exhaustion and is often invoked as the main cause for teacher attrition (Chaplain, 2008;Gonzales et al, 2020;Han et al, 2020;Skaalvik & Skaalvik, 2017). Teaching related stress and job satisfaction are related to student behavior and his/her learning and behavioural abilities, this explaining the significantly higher professional teachers' dissatisfaction and anxiety when working with students with learning difficulties (Klassen, 2010;Lobosco & Newman, 1992;Stempien & Loeb, 2002).…”
Section: Introductionmentioning
confidence: 99%